The brain - Halula, Wes; Halula, Jenica (Learning ZoneXpress, 2010)
[v.1] Physical activity and quality sleep are both vital for healthy bodies. Also, studies suggest that doing "nothing", and even being bored, is actually very important to how we process the world around us, and is key to creativity.